"ANIMATED VIDEO MEDIA": IMPROVED CONCEPTUAL UNDERSTANDING AND SOLVING MATHEMATICAL PROBLEMS - Mariam Nasution; Helmi Lailia (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
Abstract:  Today's educational requirements for entering society 5.0 include requirements for being able to change with the times. The availability of technology plays a significant role and can act as a bridge for educators and students to develop cognitive abilities including conceptual understanding and quantitative problem-solving in the classroom. The study's objectives are to evaluate (1) the ADDIE model's application to the development of animated video media, and (2) the impact of this media on students' conceptual comprehension and capacity for mathematical problem-solving. The method used in the form of Research and Development (R&D) with data collection techniques in the form of observations, interviews, tests and questionnaires with the research population is class VIII-A students with a total of 24 students. Meanwhile, the analysis used inferential statistics in the form of t-test and NGain and descriptive statistics in the form of percentages. Meanwhile, the population of VIII MTs Negeri 6 Mandailing Natal school for the 2020/2021 school year in class VIII-A is 24 students. (1) The study's invention, an ADDIE model with reliable and applicable test results, is one of its findings;(2) The effectiveness of anismation video media may be said to be effective (70.32) for resolving student issues and has a significant impact with a value of (0.00 0.05). However, it can be argued that it is effective (78.4) for helping students learn concepts. The findings of the research and development study on animated videos are significant for enhancing concept comprehension and helping students in the classroom solve mathematical issues. Abstrak: Dewasa ini, memasuki society 5.0 dunia pendidikan memiliki tuntutan berderet untuk dapat beradaptasi perkembangan zaman. Eksistensi teknologi menjadi peranan penting dan dapat menjadi perantara pendidik dan terdidik untuk meningkatkan keterampilan berpikir seperti pemahaman konsep dan pemecahan masalah matematis di kelas. Tujuan penelitian untuk menganalisis (1) Pengembangan media video animasi dengan model ADDIE; (2) Efektivitas media video anismasi terhadap pemahaman konsep dan pemecahan masalah matematis peserta didik. Metode yang digunakan berupa Research and Development (R&D) dengan teknik pengumpulan data berupa observasi, wawancara, tes dan angket dengan populasi penelitian adalah siswa kelas VIII-A dengan jumlah 24 siswa. Adapun, analisis yang digunakan statistik inferensial berupa t-test dan NGain serta statistik deskriptif berupa persentase. Adapun, populasi VIII MTs Negeri 6 Mandailing Natal school tahun ajaran 2020/2021 pada kelas VIII-A yang berjumlah 24 siswa. Hasil penelitian meliputi (1) Pengembangan yang digunakan berupa model ADDIE dengan hasil pengujian valid dan praktis; (2) Efektivitas media video anismasi dapat dikatakan efektif (78,4)untuk pemahaman konsep peserta didik dan berpengaruh secara signifikan dengan nilai (0,00 <0,05) Sedangkan efektivitas media video anismasi dapat dikatakan efektif (70,32) untuk pemecahan masalah peserta didik dan berpengaruh secara signifikan dengan nilai (0,00 < 0,05). Simpulan pada studi penelitian dan pengembangan video animasi memiliki signifikansi terhadap peningkatan pemahaman konsep dan pemecahan masalah matematis peserta didik di kelas